The Policy of Utilizing Online Applications SAYANG WARGA at Surabaya as Seen from Maqasid Syariah Perspective - Rachman, Rio Febriannur (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2023)
This study discusses one of the policies implemented by the Surabaya City Government. The policy is the utilizing online application SAYANG WARGA (Surabaya Citizen Service and Assistance System) to collect data on community health conditions. This data collection is real-time or factual, because it involves cadres who come from among the residents themselves. In the context of this research, SAYANG WARGA is not only about the applications, but also about interventions carried out by City Government to follow up on findings. Thus, SAYANG WARGA innovation is discussed using a number of theories: public policy, technological determination, Maqasid Syariah, and the concept of Sustainable Development Goals of United Nation. This study is qualitative research with a literature review approach. Research data comes from books, print and online literature, as well as mass media documentation. The results of this study show; firstly, SAYANG WARGA is a participatory public policy. It involves legislatives members and the public, through social media, to participate in monitoring. Secondly, the City Government policy is done to provide public services, in line with the challenges of the new media era. Thirdly, this policy is general, in accordance with the principles of Maqasid Syariah Al-Ammah, in the aspect of protection for: soul, mind and offspring. These three things are closely related to a person’s physical health condition, which is the focus of the policy. Fourthly, SAYANG WARGA is in line with two points of Sustainable Development Goals, such as: Good Health and Well Being; and Sustainable Cities and Communities.